Estudo molecular dos genes candidatos a melhora nos níveis de força e velocidade em atletas de domínio de alto rendimento - Ribas, Marcelo Romanovitch (2014)
Introduction: The human physical capacity is in influenced by environmental and genetic factors. The associate to genetics and the sport has the possibility to identify individuals with the greater capacity to respond or adapt to for training with lower chances of suffering from lesions. Objective: evaluate the frequency of the genes, ACTN and the ACE I/D, in fighters of dominion. Methodology: Were part of the present research 23 athletes, with 11 fighters of judo, 4 fighters of wrestling and 8 fighters of jiu jitsu, all male with a mean age 27.3±6,9 years. With national and international experience into their respective weight categories and modalities. Genotyping of the polymorphism in the ACTN3 and ACE I/D was performed by reaction polymerase chain (PCR) from DNA genomic. The frequencies genotypic and allelic were compared with control populations and athletes by the tests of chi-square and fishers exact, for all analyzes was adopted p˂0.05. Results: the frequencies genotypic and allelic of ACTN3 (RR=52.2%,RX=26.1% e XX=21.7%; R=65.2% e X=34.8%) and the ACE I/D (DD=50%, ID=25% of II=25%; D=65,2% e I=34,8% did not differ significantly on the population control. However when compared the athletes of struggle was found a meaningful difference. Conclusion: In conclusion the data of the data of the present survey indicate an associate of the gene of ACTN3 and the ACE I/D with fighter‟s domain.